Evaluasi Penggunaan Antibiotik Profilaksis Pada Pasien Bedah Sesar (Sectio Caesarea) Di Rumah Sakit Siloam Palembang. - Yessy Mia Wardhani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Delivery in Indonesia by caesarean section is increasing every year. Labor performed by cesarean section is quite susceptible to the occurrence of an infection, so that prophylactic antibiotics can be prevented. Prophylactic antibiotics themselves are antibiotics that are given before the patient enters the operating room which aims to reduce the risk of infections associated with complications and postoperative infections. The purpose of this research is to evaluate the description of the use of prophylactic antibiotics used in sectio caesarea patients at Siloam Hospital Palembang.This research is a non-experimental research with descriptive method and retrospective data collection. The data used in this study sample were 148 patients in the period from April to May 2020 and the data was obtained from the medical records of Palembang Siloam Hospital. From the research results, it was found that the antibiotic that was widely used was the third generation cephalosporin antibiotic, namely Cefoperazone which was given intravenously. The suitability of antibiotic use in caesarean section patients compared to the Hospital Formulary is in accordance with POGI (Indonesian Association of Gynecological Obstetrics), ASHP Therapeutic Guidelines, the right indication is appropriate, the patient is right, the right drug and the right dose.